Cytotoxicity and proliferative capacity impairment induced on human brain cell cultures after short‐ and long‐term exposure to magnetite nanoparticles. Issue 3 (2nd August 2016) - Coccini, Teresa; Caloni, Francesca; Ramírez Cando, Lenin Javier; De Simone, Uliana
Abstract: Since magnetic iron oxide nanoparticles (IONP) as magnetite (Fe3 O4 NPs) have potential applications in life sciences, industrial fields and biomedical care, the risks for occupational, general population and patients rises correspondingly. Excessive IONP accumulation in central nervous system (CNS) cells can lead to a disruption of normal iron metabolism/homeostasis, which is a characteristic hallmark resembling that of several neurodegenerative disorders. Fe3 O4 NPs‐ versus Fe3 O4 bulk‐induced toxic effects have been assessed in two human CNS cells namely astrocytes (D384) and neurons (SH‐SY5Y) after short‐term exposure (4–24‐48 h) to 1–100 μg ml −1, and long‐term exposure to lower concentrations. Short‐term Fe3 O4 NPs induced significant concentration‐ and time‐dependent alterations of mitochondrial function in D384 (25–75% cell viability decrease): effects started at 25 μg ml −1 after 4 h, and 1 μg ml −1 after 48 h. SH‐SY5Y were less susceptible: cytotoxicity occurred after 48 h only with 35–45% mortality (10–100 μg ml −1 ). Accordingly, a more marked intracellular iron accumulation was observed in astrocytes than neurons. Membrane integrity was unaltered in both CNS cell types. Lowering Fe3 O4 NP concentrations (0.05–10 μg ml −1 ) and prolonging the exposure time (up to 10 days), D384 toxicity was again observed (colony number decrease at ≥0.05 μg ml −1, morphology alterations and colony size reduction at ≥0.5 μg ml −1 ). Effects on SH‐SY5Y appeared at the highest concentration only. Fe3 O4 bulk was always remarkably toxic toward both cells. In summary, human cultured astrocytes were susceptible to both Fe3 O4 NP and bulk forms following short‐term and extended exposure to low concentrations, while neurons were more resistant to NPs. Cellular iron overload may trigger adverse responses by releasing iron ions (particularly in astrocytes) thus compromising the normal functions of CNS. Copyright © 2016 John Wiley & Sons, Ltd. Abstract : Human cultured astrocytes were susceptible to short‐ and long‐term Fe3 O4 nanoparticle (NP) exposure, i.e., (i) 4–48 h incubation to 1–100 μg ml −1 affected the mitochondrial function without altering cell membrane integrity, and (ii) several days of exposure to lower NP concentrations (≥ 0.05 μg ml −1 ) altered growth and cell proliferation. SH‐SY5Y neurons were more resistant to NP exposure. Fe3 O4 bulk was always remarkably toxic toward both cells. Cellular iron overload may trigger adverse responses by releasing iron ions (particularly in astrocytes) thus compromising the normal functions of CNS.